Catalytic Dry Reforming for Biomass‐Based Fuels Processing: Progress and Future Perspectives. Issue 8 (17th June 2016) - Colmenares, Juan Carlos; Colmenares Quintero, Ramón Fernando; Pieta, Izabela S.
Abstract: We describe and review recent research on potential biomass‐derived fuels consisting of methanol, ethanol, butanol, and carboxylic acids. These fuels possess a volumetric energy densities of 15.6–22.7, 20.9–26.8, and 24.6 (levulinic acid) MJ L −, respectively. We recognize biomass as a valuable, sustainable, and economic fuel source in comparison to fossil fuels. First, we discuss, characterize, and compare all mentioned fuels. Second, we review recent research developments in the continuous pre‐processing for syngas production for biofuels production, specifically concentrating on dry reforming and the catalytic effects on the effluent and process efficiency. Finally, we discuss the future prospects and research needs to realize this technology on a global scale. Abstract : Future perspectives : Imagine a world where two wastes (lignocellulosic biomass and CO2 ) will be the sources of fuels, chemicals, and commodities thanks to the use of less‐expensive transition‐metal‐based catalysts in a low‐temperature dry reforming process. A critical vision of this kind of world is presented in this Review.